Guide to hydraulic characteristics of South African rivers. - Desai, Ahmed Yacoob (My University, 2008)
Abstract The National Water Act (No. 36 of 1998) requires Ecological Reserves to be determined in order to protect the aquatic ecosystems of the water resources. Instream Flow Requirements (FRs) were established to determine these Ecological Reserves. In order to effectively determine IFRs, hydraulic parameters such as water depth, flow velocity, wetted perimeter and water surface width as functions of flowrate are required. The initial step in obtaining these parameters is to estimate a roughness coefficient to represent the resistance for the site when data is being collected. Many methods exist to aid the hydraulic practitioner in estimating roughness coefficients but they are limited in that they do not represent South African conditions, especially the large-scale roughness regime which is the most important regime in IFR studies. A review of the various resistance phenomena and roughness estimation methods was done to identify how estimations of roughness coefficients for South African rivers can improve. It was found that photographic matching was commonly used due to its simplicity and thus an electronic, using MS Access, photographic matching guide was developed using past IFR studies of South African. The guide presents photographs and hydraulic parpmeters for 79 IFR sites.